2009
DOI: 10.1111/j.1464-410x.2009.08467.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased vascular endothelial growth factor expression in patients with bladder pain syndrome/interstitial cystitis: its association with pain severity and glomerulations

Abstract: OBJECTIVE To determine the angiogenic profiles in the bladder of patients with bladder pain syndrome (BPS)/interstitial cystitis (IC), and to evaluate the relationship between these profiles and associated clinical features including pelvic pain and glomerulations. PATIENTS AND METHODS Angiogenesis and angiogenic components are important in chronic inflammatory disease. High levels of vascular endothelial growth factor (VEGF) have been shown to induce immature angiogenesis, where microvessels have insufficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
77
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 22 publications
(37 reference statements)
5
77
0
Order By: Relevance
“…The severity of neuronal and myogenic damage is established considering the degree of oxidative stress, revealing the symptomatology of the disease. Although it is not yet clear whether it is a cause or a result, it is obvious that there are some microvascular changes causing oxidative stress in BPS/IC and that mature vessel elements [29], and therefore, blood flow to the bladder decrease in these patients. It has been shown in previous studies that BPS/IC coexists and resembles allergic diseases such as bronchial asthma and allergic rhinitis where mast cell activation and histamine secretion are seen [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…The severity of neuronal and myogenic damage is established considering the degree of oxidative stress, revealing the symptomatology of the disease. Although it is not yet clear whether it is a cause or a result, it is obvious that there are some microvascular changes causing oxidative stress in BPS/IC and that mature vessel elements [29], and therefore, blood flow to the bladder decrease in these patients. It has been shown in previous studies that BPS/IC coexists and resembles allergic diseases such as bronchial asthma and allergic rhinitis where mast cell activation and histamine secretion are seen [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…To date, the pathogenesis of cystoscopic glomerulations is not yet fully understood. Tamaki et al [21] and Kiuchi et al [22] found cystoscopic glomerulations to be highly associated with the overexpression of angiogenic growth factors in the bladder. In addition, Kiuchi et al [22] found that the expression of angiogenic growth factor is associated with the degree of pain described by IC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Tamaki et al [21] and Kiuchi et al [22] found cystoscopic glomerulations to be highly associated with the overexpression of angiogenic growth factors in the bladder. In addition, Kiuchi et al [22] found that the expression of angiogenic growth factor is associated with the degree of pain described by IC patients. Thus, it seems likely that neovascularization promoted by angiogenic growth factors has an important role in the pathogenesis of glomerulations and IC.…”
Section: Discussionmentioning
confidence: 99%
“…However, a working hypothesis is that regardless of the cause of urothelial injury, i.e., BCG, bacterial infection, or any noxious substance in the urine, the urinary bladder responds by increasing the production of VEGF that acts initially as a survival factor (16) but also has the capacity of increasing vascular permeability (24), leading to glomerulations (34,69), edema, and inflammation. The present findings add to existing evidence indicating that, in the urinary bladder, NRPs are expressed in the urothelium, immune cells, nerves, blood vessels, and lymphatic vessels and mediate the accumulation of VEGF tracer.…”
Section: Discussionmentioning
confidence: 99%